TAAC - TMS Adaptable Auditory Control: A universal tool to mask TMS clicks - Russo, S.; Sarasso, S.; Puglisi, G.E.; Dal Palù, D.; Pigorini, A.; Casarotto, S.; D’Ambrosio, S.; Astolfi, A.; Massimini, M.; Rosanova, M.; Fecchio, M. (Journal of neuroscience methods, 2022)
Coupling transcranial magnetic stimulation with electroencephalography (TMS-EEG) allows recording the EEG response to a direct, non-invasive cortical perturbation. However, obtaining a genuine TMS-evoked EEG potential requires controlling for several confounds, among which a main source is represented by the auditory evoked potentials (AEPs) associated to the TMS discharge noise (TMS click). This contaminating factor can be in principle prevented by playing a masking noise through earphones. Here we release TMS Adaptable Auditory Control (TAAC), a highly flexible, open-source, Matlab®-based interface that generates in real-time customized masking noises. TAAC creates noises starting from the stimulator-specific TMS click and tailors them to fit the individual, subject-specific click perception by mixing and manipulating the standard noises in both time and frequency domains. We showed that TAAC allows us to provide standard as well as customized noises able to effectively and safely mask the TMS click. Here, we showcased two customized noises by comparing them to two standard noises previously used in the TMS literature (i.e., a white noise and a noise generated from the stimulator-specific TMS click only). For each, we quantified the Sound Pressure Level (SPL; measured by a Head and Torso Simulator - HATS) required to mask the TMS click in a population of 20 healthy subjects. Both customized noises were effective at safe (according to OSHA and NIOSH safety guidelines) and lower SPLs with respect to standard noises. At odds with previous methods, TAAC allows creating effective and safe masking noises specifically tailored on each TMS device and subject. The combination of TAAC with tools for the real-time visualization of TEPs can help control the influence of auditory confounds also in non-compliant patients. Finally, TAAC is a highly flexible and open-source tool, so it can be further extended to meet different experimental requirements. •Auditory evoked potentials are the main confounding of the EEG responses to TMS.•We release TAAC, a flexible open-source tool that generates customized masking noises.•TAAC generates masking noises effective at lower volume compared to existing methods.